Perceived Supervisor Support as a Mediator Between Flexible Working Arrangements and Employee Performance in a Work From Home - Rachellia Abitha Daniswara; Ika Korika Swasti (International Journal of Economics and Management Sciences, 2025)
The shift towards flexible working arrangements (FWA), especially in the context of remote work or work-from-home (WFH) settings, has prompted organizations to rethink how flexibility impacts employee performance. While FWA offers potential benefits such as improved work-life balance and autonomy, it can also create challenges related to time management, coordination, and communication—particularly in the absence of adequate support from supervisors. This study addresses the problem of whether work flexibility alone is sufficient to enhance employee performance, or if perceived supervisor support (PSS) serves as a mediating factor in this relationship. The objective of this research is to investigate the role of PSS as a mediator between FWA and employee performance. A quantitative research method was employed, with data collected via structured questionnaires distributed to 35 employees working under flexible arrangements. The collected data were then analyzed using statistical techniques to assess both direct and indirect relationships among the variables. The findings indicate that while FWA does not directly improve employee performance, it significantly enhances employees’ perception of supervisor support. Furthermore, PSS was found to have a strong positive influence on performance outcomes. These results suggest that flexibility in work arrangements must be complemented by consistent and active supervisory engagement to yield positive effects on employee performance. In conclusion, the study emphasizes that PSS plays a critical mediating role in the FWA–performance link. Organizations seeking to implement or optimize flexible work policies should prioritize supervisor training and engagement strategies to ensure that flexibility translates into measurable performance improvements. Future research may explore these dynamics in larger populations and across different industries.